Character traits and involvement in immoral acts among Malay adult prisoners - Laidin, Jamaliah; Roslan, Samsilah; Md. Aroff, Abdul Rahman; Mahyiddin, Rahil; Sabouripour, Fatemeh; Ghiami, Zeinab (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This study aimed to examine the relationship between character traits and involvement in immoral acts among Malay adult prisoners. Despite increased involvement of Malay adult in immoral acts research on internal factors, such as, traits, which contribute to immoral acts involvement, is lacking. The study involved 801 respondents randomly selected from the Kajang Prison inmates in the Klang Valley. Pearson Product Moment Correlation Coefficient indicated a positive correlation between blameworthy traits and involvement in immoral acts. Moreover, the result showed a significant negative relationship between praiseworthy traits and immoral acts involvement. Multiple linear regression analysis showed that seven predictors of the Islamic character traits contribute significantly towards immoral acts involvement among Malay adult prisoners. The study focused on an overall relationship between the Malay adult prisoners’ character traits and crimes committed without linking the character traits to specific crimes. The findings suggested that teaching ethics in Islamic studies should focus on the development of Islamic moral traits and character.